Dietary autochthonous Cetobacterium somerae CSHT supplementation enhances heat tolerance in hybrid sturgeon - Zhichao Chen; Yinshan Bai; Yuanqiong Wei; Wenhua Wu; Linmiao Li; Haoting Mai; Yepin Yu; Jinping Chen; Xiujuan Zhang (Aquaculture, 2027)

A systematic identification and characterization of long noncoding RNAs during abiotic stress in Medicago truncatula - Kanghua Du; Yingan Zhu; Weiyu Yan; Ting Gao; Wanfu Mu; Ziwei Zhao; Zhong Dan; Xiaolu Meng; Haoting Chen; Yan Zhao; Jie Zhang (Journal of Plant Physiology, 2026)

LaY-Cellulose-LDO oxygen carrier derived from adsorption residues for enhanced chemical looping steam methane reforming - Jinxia Quan; Haoting Mai; Qinteng Hu; Jian Chen; Xuelin Chen; Qimeng Zeng; Zhifeng Hu (Fuel, 2026)

Corrigendum to “Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy” [Chem. Eng. J. 495 (2024) 153371] - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2026)

Underwater Noise in Offshore Wind Farms: Monitoring Technologies, Acoustic Characteristics, and Long-Term Adaptive Management - Peibin Zhu; Zhenquan Hu; Haoting Li; Meiling Dai; Jiali Chen; Zhuanqiong Hu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The rapid global expansion of offshore wind energy (OWE) has established it as a critical component of the renewable energy transition; however, this development concurrently introduces significant underwater noise pollution into marine ecosystems. This paper provides a comprehensive review of the acoustic footprint of OWE across its entire lifecycle, rigorously distinguishing between the high-intensity, acute impulsive noise generated during pile-driving construction and the chronic, low-frequency continuous noise associated with decades-long turbine operation. We critically evaluate the engineering capabilities and limitations of current underwater acoustic monitoring architectures, including buoy-based real-time monitoring nodes, cabled high-bandwidth systems (e.g., cabled hydrophone arrays with DAQ/DSP and fiber-optic distributed acoustic sensing, DAS), and autonomous seabed archival recorders (PAM deployment). Furthermore, documented biological impacts are synthesized across diverse taxa, ranging from auditory masking and threshold shifts in marine mammals to the often-overlooked sensitivity of invertebrates and fish to particle motion—a key metric frequently missing from standard pressure-based assessments. Our analysis identifies a fundamental gap in current governance paradigms, which disproportionately prioritize the mitigation of short-term acute impacts while neglecting the cumulative ecological risks of long-term operational noise. This review synthesizes recent evidence on chronic operational noise and outlines a conceptual pathway from event-based compliance monitoring toward long-term, adaptive soundscape management. We propose the implementation of integrated, adaptive acoustic monitoring networks capable of quantifying cumulative noise exposure and informing real-time mitigation strategies. Such a paradigm shift is essential for optimizing mitigation technologies and ensuring the sustainable coexistence of marine renewable energy development and marine biodiversity.

Supramolecular self-assembly for probiotic delivery in food system: responsive strategies, multifunctional carriers, future perspectives - Li Song; Haoting Xu; Chaofan Chen; Yubin Zhang; Zihao Zhang; Xiangfeng Chen; Shunxun Liu; Hang Xiao; Qing Gu; Ping Li (Trends in Food Science & Technology, 2025)

Forest biomass carbon stock estimates via a novel approach: K-nearest neighbor-based weighted least squares multiple birth support vector regression coupled with whale optimization algorithm - Niannian Deng; Renpeng Xu; Ying Zhang; Haoting Wang; Chen Chen; Huiru Wang (Computers and Electronics in Agriculture, 2025)

The involvement of thioredoxin reductase genes in development, reproduction and deltamethrin tolerance in the red flour beetle, Tribolium castaneum - Caihong Ji; Daojie Guan; Haoting Chen; Zhichao Luo; Chengyun Jian; Zhichao Wang; Huichen Ge; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2025)

Involvement of AhR/ARNT in tolerance to deltamethrin by regulating the expression of TcGSTs6 in Tribolium castaneum - Zhichao Luo; Haoting Chen; Daojie Guan; Chen Hang; Zhichao Wang; Huichen Ge; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2025)

Coexposure to ambient air pollution and temperature and its associations with birth outcomes in women undergoing assisted reproductive technology in Fujian, China: A retrospective cohort study - Dongdong Jiang; Xuefen Cai; Hua Fang; Yuehong Li; Ziqi Zhang; Haoting Chen; Zixin Zheng; Wenxiang Wang; Yan Sun (Journal of Hazardous Materials, 2025)

Cortical microstructural alterations in different stages of Parkinson’s disease - Xueqin Bai; Tao Guo; Xiaojun Guan; Cheng Zhou; Jingjing Wu; Haoting Wu; Xiaocao Liu; Chengqing Wu; Jingwen Chen; Jiaqi Wen; Jianmei Qin; Sijia Tan; et al. (Brain Imaging and Behavior, 2024)

Self-enhanced targeted nanomedicines based on iron starvation acclimation for tumor-specific therapy - Zhenxin Guan; Jinghui Hu; Song Li; Yurong Liu; Xiaokang Zhang; Jinxiang Liu; Haoting Chen; Fangling Liao; Huiting Sun; Guige Hou; Weisheng Guo; Yafang Xiao; et al. (Chemical Engineering Journal, 2024)

Determinations of methylmercury and mercury methylation/demethylation rate constants in environmental samples using isotope dilution/tracing methods by automatic ethylation-purge and trap-GC-ICP-MS - Yandong Liu; Xueyu Guo; Jinqian Ju; Haoting Gong; Huijing Wang; Lufeng Chen; Yanqun Liu; Pu Wang; Yong Liang (Analytica Chimica Acta, 2024)

Antibody-based near-infrared fluorogenic probes for wash-free imaging of cell-surface proteins - Haoting Wang; Jiaqi Yan; Wenchao Wang; Endong Chen; Di Chen; Su Zeng; Quan Li; Linghui Qian (Analytica Chimica Acta, 2024)

Association of ambient air pollution and pregnancy rate among women undergoing assisted reproduction technology in Fujian, China: A retrospective cohort study - Hua Fang; Dongdong Jiang; Ye He; Siyi Wu; Yuehong Li; Ziqi Zhang; Haoting Chen; Zixin Zheng; Yan Sun; Wenxiang Wang (Science of The Total Environment, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Mechanistic insights into surface catalytic oxidation of fluoroquinolone antibiotics on sediment mackinawite - Xiru Chen; Zeyu Xian; Song Gao; Lihua Bai; Sijia Liang; Haoting Tian; Chao Wang; Cheng Gu (Water Research, 2023)

Identification of novel genes in Behcet’s disease using integrated bioinformatic analysis - Si Chen; Haolong Li; Haoting Zhan; Xiaoli Zeng; Hui Yuan; Yongzhe Li (Immunologic Research, 2022)
Behcet’s disease (BD) is a chronic vascular inflammatory disease. However, the etiology and molecular mechanisms underlying BD development have not been thoroughly understood. Gene expression data for BD were obtained from the Gene Expression Omnibus database. We used robust rank aggregation (RRA) to identify differentially expressed genes (DEGs) between patients with BD and healthy controls. Gene ontology functional enrichment was used to investigate the potential functions of the DEGs. Protein–protein interaction (PPI) network analysis was performed to identify the hub genes. Receiver operating characteristic analyses were performed to investigate the value of hub genes in the diagnosis of BD. GSE17114 and GSE61399 datasets were included, comprising 32 patients with BD and 26 controls. The RRA integrated analysis identified 44 significant DEGs among the GSE17114 and GSE61399 CD4 + T lymphocytes. Functional enrichment analysis revealed that protein tyrosine/threonine phosphatase activity and immunoglobulin binding were enriched in BD. PPI analysis identified FCGR3B as a hub gene in the CD4 + T lymphocytes of BD patients. Our bioinformatic analysis identified new genetic features, which will enable further understanding of the pathogenesis of BD.

Cholinergic relevant functional reactivity is associated with dopamine responsiveness of tremor in Parkinson’s disease - Jingjing Wu; Cheng Zhou; Tao Guo; Xiaojun Guan; Ting Gao; Xueqin Bai; Haoting Wu; Jingwen Chen; Jiaqi Wen; Xiaocao Liu; Luyan Gu; Zhe Song; et al. (Brain Imaging and Behavior, 2022)
Tremor in Parkinson’s disease (PD) has distinct responsiveness to dopamine, which is supposed not be exclusively related to dopamine deficiency but has a close relationship with cholinergic system. This phenomenon indicates that cholinergic system may be an important regulatory for distinct dopamine responsiveness of parkinsonian tremor. Through investigating the alterations of cholinergic and dopaminergic network during levodopa administration, we aimed at exploring the mechanisms of differed dopamine responsiveness of parkinsonian tremor. Fifty-two PD patients with tremor were enrolled. MRI scanning, UPDRS III and its sub-symptom scores were collected in OFF and ON status (dopaminergic challenge test). Then, patients were divided into two groups (dopamine-resistant tremor and dopamine-responsive tremor) according to the tremor change rate median score. Dopaminergic and cholinergic network were obtained. LASSO regression was conducted to identify functional connectivity with distinct reactivity during levodopa administration between groups. Afterwards, detailed group comparisons, interaction and correlation analyses were performed. The reactivity of cholinergic connectivity showed the highest possibility to distinguish two groups, especially connectivity of right basal forebrain 123 to right parietal operculum cortex (R.BF123-R.PO). After levodopa administration, connectivity of R.BF123-R.PO was decreased for dopamine-responsive tremor while which remained unchanged for dopamine-resistant tremor. The reactivity of R.BF123-R.PO was negatively correlated with tremor change rate. Reduced cholinergic connectivity to parietal operculum may be an underlying mechanism for the responsive tremor in PD and the distinct cholinergic reactivity of parietal operculum to levodopa may be a core pathophysiology for the differed DA responsiveness of tremor in PD.